How different an emotional competence profile can be, when we became slim? – longitudinal case study - Veiga-Branco, Augusta (2012)
This case study focuses on Emotional Competence (Saarni, 2000; Veiga Branco, 2004, 2007), the concept redefined from the initial Emotional Intelligence (Mayer-Salovey, 1990, 1997, Goleman, 1995), here applied, to perceive the behavioral differences when someone lost 43Kg of body weight, without pathology associated. The longitudinal research compares, the behavior profile, before (obese) and after (non obese) a weight loss, through Self-conscience, Self-motivation, Emotions Management, Empathy and Emotions Management in Group Qualitative and longitudinal study (three years), conducted through deep interviews with two instruments: Firstly, "Emotional Competence Veiga Scale" and an "Interview guide", along these years. The case study is about a 22-26 year old, male, with 122Kg (initially) and 69Kg now. The weight loss was personally induced by phytotherapy treatment in healthy process, 8 months long.The CE profile shows some differences, in attitudes and way of life, that have as a consequence the different behaviour of the subject. - The initial (obese) Self-conscience profile was focused in external joy evidences and social relational interaction, but - when alone - with episodes of rumination and negative emotions, that now (thin) the subject "does not value much"; - Emotions Management (before) associated to distance related - feelings of disregarded - even often eating chocolate while studying or at night, but since he’s slim (now) he feels distancing attitudes, introversion, apathy and sadness that he tries to hide. - There are less valued Self-motivation, empathy and emotion management in a group, because they are perceived as less relevant, than before. When thin, the subject has a perception of a good self-conscience – before because joy and group interaction, now because self-image, and a no suffer emotions profile. Thin present profile is centralized in less positive and weak self-concept.